WebSphere Business Integration Message Broker basics - Davies, Saida (IBM redbooks., 2004)
This IBM Redbooks publication provides an overview of the latest release of WebSphere Business Integration Message Brokers and the new Message Brokers Toolkit for WebSphere Studio. It covers the following topics: - Installing WebSphere Business Integration Message Broker and WebSphere Business Integration Event Broker on Windows - Creating and verifying a default configuration - Developing a simple message flow and message set in the Message Brokers Toolkit - Deploying a message flow application to a broker - Diagnosing and fixing problems The book also describes where to find more information, including product documentation and sample applications.